2007
DOI: 10.1016/j.jmb.2007.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli tatC Mutations that Suppress Defective Twin-Arginine Transporter Signal Peptides

Abstract: In vitro studies have suggested that the TatBC complex serves as the receptor for signal peptides targeted for export via the twin-arginine translocation (Tat) pathway. Substitution of the hallmark twin-arginine dipeptide with two lysines abrogates export of physiological substrates in all organisms. We report the isolation and characterization of suppressor mutations that allow export of an ssTor(KK)-GFP-SsrA tripartite fusion. We identified two amino acid suppressor mutations in the first cytoplasmic loop of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 35 publications
5
62
0
Order By: Relevance
“…We would predict that this recognition occurs deeper in the membrane. Recent findings indicate that an RR signal peptide must be able to interact with TatBC also within the plane of the lipid bilayer: some suppressor mutations of a KQ variant of TorA-MalE map to the N terminus of TatB predicted to lie on the trans-side of the membrane (17) as well as to a predicted periplasmic loop of TatC (18). Substitution of Phe for Val two residues downstream of the RR pair of the thylakoid precursor tOE17 results in a protease-resistant insertion of the signal sequence into the thylakoid Hcf106-cpTatC receptor (50), which together with other results prompted these authors to suggest a similar two-stage binding model.…”
Section: Discussionmentioning
confidence: 99%
“…We would predict that this recognition occurs deeper in the membrane. Recent findings indicate that an RR signal peptide must be able to interact with TatBC also within the plane of the lipid bilayer: some suppressor mutations of a KQ variant of TorA-MalE map to the N terminus of TatB predicted to lie on the trans-side of the membrane (17) as well as to a predicted periplasmic loop of TatC (18). Substitution of Phe for Val two residues downstream of the RR pair of the thylakoid precursor tOE17 results in a protease-resistant insertion of the signal sequence into the thylakoid Hcf106-cpTatC receptor (50), which together with other results prompted these authors to suggest a similar two-stage binding model.…”
Section: Discussionmentioning
confidence: 99%
“…Hereafter, we focused our attention on the class I suppressors. To determine whether class I suppression was related to intracellular abundance of translocase proteins, the expression level of the mutant Tat proteins was analyzed by immunoblotting (14,15). Nearly equal amounts of TatA were detected in membranes from cells expressing wt and mutant Tat translocases, whereas subtle differences in TatB expression were observed (Fig.…”
Section: Isolation Of Mutant Tatabc Translocases That Suppress Foldinmentioning
confidence: 99%
“…S3). Initial attempts to detect TatC were unsuccessful, likely because of the low expression level from pBR322, as was reported (15). To circumvent this problem, a small epitope tag was fused to the C terminus of TatC, which is known to tolerate C-terminal fusions without loss of function (15).…”
Section: Isolation Of Mutant Tatabc Translocases That Suppress Foldinmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we wanted to determine if PhoD SP -GFP was secreted in a Tatdependent manner. Toward this end, we generated strains that contained individual and double deletions of the two known Tat signal peptide recognition proteins, TatCd and TatCy (24)(25)(26)71). qRT-PCR, fluorescent images of expressing cells, and Western blot analysis indicated that each Tat deletion strain expressed PhoD SP -GFP at similar levels (see Table S3 and Fig.…”
Section: Resultsmentioning
confidence: 99%